Acute physiological and psychophysical responses to different modes of heat stress. Issue 5 (16th March 2022) - Campbell, Holly A.; Akerman, Ashley P.; Kissling, Lorenz S.; Prout, Jamie R.; Gibbons, Travis D.; Thomas, Kate N.; Cotter, James D.
Abstract : New Findings: What is the central question of this study? What are the profiles of acute physiological and psychophysical strain during and in recovery from different modes of heating, and to what extent do these diminish after repeated exposure? What is the main finding and its importance? Mode of heating affects the strain profiles during heat stress and recovery. Exercise in the heat incurred the greatest cardiovascular strain during heating and recovery. Humid heat was poorly tolerated despite heat strain being no greater than in other heating modes, and tolerance did not improve with multiple exposures. Abstract: Heat stress is common and arises endogenously and exogenously. It can be acutely hazardous while also increasingly advocated to drive health and performance‐related adaptations. Yet, the nature of strain (deviation in regulated variables) imposed by different heating modes is not well established, despite the potential for important differences. We, therefore, compared three modes of heat stress for thermal, cardiovascular and perceptual strain profiles during exposure and recovery when experienced as a novel stimulus and an accustomed stimulus. In a crossover design, 13 physically active participants (five females) underwent 5 days of 60‐min exposures to hot water immersion (40°C), sauna (55°C, 54% relative humidity) and exercise in the heat (40°C, 52% relative humidity), and a thermoneutral water immersion control (36.5°C), each separated by ≥4 weeks. Physiological (thermal, cardiovascular, haemodynamic) and psychophysical strain responses were assessed on days 1 and 5. Sauna evoked the warmest skin (40°C; P < 0.001) but exercise in the heat caused the largest increase in core temperature, sweat rate, heart rate ( post hoc comparisons all P < 0.001) and systolic blood pressure ( P ≤ 0.002), and possibly decrease in diastolic blood pressures ( P ≤ 0.130), regardless of day. Thermal sensation and feeling state were more favourable on day 5 than on day 1 ( P ≤ 0.021), with all modes of heat being equivalently uncomfortable ( P ≥ 0.215). Plasma volume expanded the largest extent during immersions ( P < 0.001). The current data highlight that exercising in the heat generates a more complex strain profile, while passive heat stress in humid heat has lower tolerance and more cardiovascular strain than hot water immersion.